Pengetahuan dan Sikap Ibu Nifas Suku Batak Toba dalam Manajemen ASI Eksklusif di UPTD Puskesmas Pematang Sidamanik Tahun 2024 - Laura Sihombing; Eli Oktarina; Elsa Siburian; Emmi Mauliana; Laeli Yuliyanti; Debora Paninsari (Jurnal Kebidanan Harapan Ibu Pekalongan, 2025)
The success of exclusive breastfeeding is highly dependent on the stages of exclusive breastfeeding management. Each stage must be carefully prepared to ensure its success. Exclusive breastfeeding management includes all initiatives aimed at helping women successfully breastfeed their babies. This study aims to assess the knowledge and attitudes of Batak Toba postpartum mothers about exclusive breastfeeding management. This study is quantitative using descriptive methodology. The population of this study consisted of 139 postpartum mothers at the UPTD Pematang Sidamanik Health Center from January to September 2024. The sampling method used was purposive sampling with a sample size of 32 respondents. The research tools used questionnaires and consent forms. The results showed that of the 32 respondents, the majority of postpartum mothers had a good understanding of exclusive breastfeeding management, with 27 people (84.4%) showing good knowledge. Conversely, 15.6% showed sufficient knowledge, while 23 respondents (71.9%) were positive, and 9 people (28.1%) were negative. Postpartum mothers at the UPTD Pematang Sidamanik Health Center have sufficient knowledge and have a positive attitude towards the management of exclusive breastfeeding.